Pengaruh Terciptanya Effective Leadership, Psychological Safety, Lack of Social Connection terhadap Job Retention di PTPN IV Regional 1 Medan - Debie Merry Eunike Hutagalung; Junika Napitupulu; Jon Henri Purba (Universitas Methodist Indonesia, 2026)
This study aims to analyze the influence of effective leadership, psychological safety, and lack of social connection on employee job retention at PTPN IV Regional I Medan. A quantitative approach was used with a survey method involving 60 respondents. Data were collected through questionnaires that met validity (r > 0.254) and reliability (Cronbach’s alpha > 0.70) requirements. Data analysis employed multiple linear regression after passing classical assumption tests. The results indicate that effective leadership has a positive and significant effect on job retention (t = 4.215) and psychological safety also has a positive and significant effect (t = 3.876), while lack of social connection has a negative and significant effect (t = −2.945). Simultaneously, all variables significantly influence job retention (F = 28.614; p < 0.05) with an adjusted R² value of 0.581. These findings highlight the importance of effective leadership, psychological safety, and social connectedness in improving employee retention